To sense or not to sense—new insights from GPCR-based and arrestin-based biosensors. (April 2019) - Haider, Raphael Silvanus; Godbole, Amod; Hoffmann, Carsten
Abstract : Advances in resolving crystal structures of GPCRs and their binding partners as well as improvements in live-cell microscopy and the fluorescent proteins pallet has greatly driven new ideas for designing optical sensors for the same. Sensors have been developed to monitor ligand binding as well as the ensuing ligand-induced conformational changes in GPCRs, G-proteins and arrestins. In this review we will highlight the functionality of such sensor designs starting from monitoring ligand binding to receptor activation and interaction with arrestins. Furthermore, we will highlight the importance of sensor designs to monitor receptor-dependent arrestin conformations and give an idea about the various detected arrestin conformations and their possible implications.